Membangun Generasi Sehat dan Mandiri Pangan melalui Sosialisasi Sanitasi, Peternakan, Hidroponik di Desa Jendi - Aulia, Titania (Bakti Cendana, 2024)
Activities to build a healthy and self-sufficient generation of food through socialization on sanitation, animal husbandry and hydroponics in Jendi Village are carried out through three programs. The first program is integrated livestock socialization, which is carried out through door-to-door socialization to breeders in Jendi Village. The program intend to increase the efficiency of production and reproduction of livestock with high nutritional animal feed. The second program is optimizing the yard with hydroponics which is carried out with a wick system for PKK women in Jendi Village. The program intend to take advantage of the home page and agricultural productivity of the Jendi Village residents. While the third program is a movement for healthy living with nutritious food and love for the environment from an early age using the socialization method in the form of counseling to children in grades 1-3 at SDN 2 Jendi. The program intend to educate children about personal hygiene, nutritious food, and how to grow plants for the school yard.